Predictors of Bronchopulmonary Dysplasia Formation - Ye.N. Okhotnikova; Ye.V. Sharikadze (Zaslavsky O.Yu., 2013)
The authors studied and analyzed a group of prenatal, intra-, and neonatal factors leading to the development of bronchopulmonary dysplasia (BPD). Nnegative impact of BPD on the development of chronic bronchopulmonary pathology in children in the first three years of life was determined.